Arquitetura dos terminais de passageiros em aeroportos: panorama histórico, estudo de tipologias e possibilidades de ampliação - Salgueiro, Francisco Angotti de Carvalho (2006)
Terminal Passengers represents one of the most distinctive building types of architecture nowadays and a field of formal and technological experiments that unfolds itself in a series of typologies. Since the beginning of the 20th century, airports equipments were transformed and evolved into different proportions, specially after jet times, in order to optimise the flow, reducing the walking distances for passengers: from terminals to planes. The terminals were rebuilt and extended to adapt to changes and expansion of commercial flight and airplane dimensions; redesigned by architects and following the engineering technical improvements, terminals have come through innovations, which typological classification is one of the main themes of this research. The other subjects developed are: a historical panorama of the international architecture of airports, the birth of Brazilian architecture in this field, and an emphasis on the study of the typologies of some of the most important terminals of Europe, United States and Asia. A sequence of case studies, accompanied by several images composing an iconographic dossier, synthesizes into a classification of contemporary projects of terminal building types, analysing its possibilities of extension.